A network analysis in adolescent anorexia nervosa exploring the connection between both patient and carer reactions and outcome. (19th June 2022) - Monteleone, Alessio Maria; Cascino, Giammarco; Salerno, Laura; Schmidt, Ulrike; Micali, Nadia; Cardi, Valentina; Treasure, Janet
Abstract: Objective: This paper used network analysis to test the associations between eating disorder‐related psychopathology and carers' responses to anorexia nervosa symptoms in adolescents. Additionally, the prognostic value of central and bridge network nodes was explored. Method: This is a secondary analysis of a three‐armed randomised‐controlled‐trial of adolescents with anorexia nervosa ( n = 149) and their primary carer ( n = 149) who were allocated to either treatment as usual (TAU), or one of two versions of a carer skills intervention (ECHO) added to TAU. A network analysis was run in the full sample. The prognostic role of central and bridge nodes was tested through multiple regression analyses. Results: Carers' depression and emotional over‐involvement, as well as patients' depression showed the highest strength centrality. Patients' depression and carers' accommodation exhibited the highest bridge expected influence. Across the full sample, and in the ECHO group, carers' accommodation predicted patients' higher body mass index (BMI), while patients' depression predicted worse psychosocial functioning at 1‐year follow‐up. In the ECHO group, higher carers' depression also predicted lower BMI. Conclusions: Carers' accommodation and depression in both carers and patients were involved in the maintenance of psychopathology in adolescents with anorexia nervosa. Depression in both patients and carers is a potential treatment target for family interventions. Key points: Accommodation is the carers' variable most connected with adolescents' symptoms and is positively associated with adolescents' BMI at 1 year follow‐up. Depression is the adolescents' symptom most connected with carers' functioning and predicts impaired psychosocial functioning at 1 year follow‐up. carers' depression contributes to the maintenance of anorexia nervosa psychopathology and is negatively associated with adolescents' BMI at 1 year in ECHO treatment group.